NMR analysis of a 900K GroEL–GroES complex - Fiaux, Jocelyne; Bertelsen, Eric B.; Horwich, Arthur L.; Wüthrich, Kurt (Nature (London), 2002)
Biomacromolecular structures with a relative molecular mass ( M r ) of 50,000 to 100,000 (50K–100K) have been generally considered to be inaccessible to analysis by solution NMR spectroscopy. Here we report spectra recorded from bacterial chaperonin complexes ten times this size limit (up to M r 900K) using the techniques of transverse relaxation-optimized spectroscopy and cross-correlated relaxation-enhanced polarization transfer 1 , 2 , 3 , 4 , 5 . These techniques prevent deterioration of the NMR spectra by the rapid transverse relaxation of the magnetization to which large, slowly tumbling molecules are otherwise subject. We tested the resolving power of these techniques by examining the isotope-labelled homoheptameric co-chaperonin GroES ( M r 72K), either free in solution or in complex with the homotetradecameric chaperonin GroEL ( M r 800K) or with the single-ring GroEL variant SR1 ( M r 400K). Most amino acids of GroES show the same resonances whether free in solution or in complex with chaperonin; however, residues 17–32 show large chemical shift changes on binding. These amino acids belong to a mobile loop region of GroES that forms contacts with GroEL 6 , 7 , 8 , 9 , 10 . This establishes the utility of these techniques for solution NMR studies that should permit the exploration of structure, dynamics and interactions in large macromolecular complexes.